Abnormalities in Brainstem Auditory Evoked Potentials in Sheep with Transmissible Spongiform Encephalopathies and Lack of a Clear Pathological Relationship - Konold, Timm; Phelan, Laura J.; Cawthraw, Saira; Simmons, Marion M.; Chaplin, Melanie J.; González, Lorenzo (Frontiers in Veterinary Science, 2016)
Scrapie is a transmissible spongiform encephalopathy (TSE), which causes neurological signs in sheep but confirmatory diagnosis is usually made postmortem on examination of the brain for TSE-associated markers like vacuolar changes and disease-associated prion protein (PrPSc). The objective of this study was to evaluate whether testing of brainstem auditory evoked potentials (BAEPs) at two different sound levels could aid in the clinical diagnosis of TSEs in sheep naturally or experimentally infected with different TSE strains [classical and atypical scrapie and bovine spongiform encephalopathy (BSE)] and whether any BAEP abnormalities were associated with TSE-associated markers in the auditory pathways. BAEPs were recorded from 141 clinically healthy sheep of different breeds and ages that tested negative for TSEs on postmortem tests to establish a reference range and to allow comparison with 30 sheep clinically affected or exposed to classical scrapie without disease confirmation (test group 1) and 182 clinically affected sheep with disease confirmation (test group 2). Abnormal BAEPs were found in seven sheep (23%) of group 1 and 42 sheep (23%) of group 2. The proportion of sheep with abnormalities did not appear to be influenced by TSE strain or prion protein gene polymorphisms. When the magnitude of TSE-associated markers in the auditory pathways was compared between a subset of 12 sheep with and 12 sheep without BAEP abnormalities in group 2, no significant differences in the total PrPSc or vacuolation scores in the auditory pathways could be found. However, the data suggested that there was a difference in the PrPSc scores depending on the TSE strain because PrPSc scores were significantly higher in sheep with BAEP abnormalities infected with classical and L-type BSE but not with classical scrapie. The results indicated that BAEPs may be abnormal in sheep infected with TSEs but the test is not specific for TSEs, and that neither vacuolation nor PrPSc accumulation appears to be responsible for the clinical abnormalities.